Recent topics related to etiology and clinical manifestations of cutaneous arteritis - Ikeda, Takaharu (Frontiers in Medicine, 2022)
Cutaneous polyarteritis nodosa (cPAN) was first reported by Lindberg in 1931. It has been recognized as a skin-limited vasculitis whose cutaneous histopathological features are indistinguishable from those of PAN. Cutaneous arteritis (CA) was defined as a form of single-organ vasculitis in the revised Chapel Hill Classification and was recognized as the same disease as cPAN. It became known that deficiency of adenosine deaminase 2 (DADA2) cases were included in cases that had been diagnosed with CA. Because of their similarity and differences in the treatment methods, DADA2 should be considered in CA cases, especially if they are diagnosed or developed in early childhood. Cutaneous arteritis may be classified as an immune complex-mediated vasculitis. It was reported that the pathogenesis of anti-lysosomal-associated membrane protein-2 (LAMP-2) antibodies and anti-phosphatidylserine-prothrombin complex (PS/PT) antibodies as good parameters in CA. The main skin manifestations include livedo racemosa, subcutaneous nodules, and ulcers. Although CA is recognized to have a benign clinical course, it has become known that it is easy to relapse. The existence of skin ulcers upon diagnosis or sensory neuropathies was suggested to be a predictor of poor prognosis. Cutaneous arteritis with them may need to be treated with more intensive therapies.